Improving Critical Thinking Skills With E-LKPD Oriented Think Pair Share For Chemical Equilibrium Material - Fajar Nova Prasetyo; Dian Novita (Universitas Pendidikan Mandalika, 2023)
Through the creation of Think Pair Share-oriented E-LKPD, This study aims to enhance the ability of pupils to think critically regarding chemical equilibrium content.. The methodology of research utilized in this study is the Research and Development (R&D) approach, which was modified from Sugiyono (2015). The limited trial used One Group Pretest-Posttest Design. This study was conducted at SMAN 12 Surabaya. The validity data come from the E-LKPD's validity results, the practicality data come from the results of student activity observation and student response questionnaires, and the effectiveness data come from the critical thinking skills and student learning outcomes pre- and post-test results. From the research findings, in terms of validity, a mode score of ≥ 3 was gained for each aspect. Practicality is shown by the results of the learner response questionnaire with a percentage of 94.76%. The n-gain score findings for students in the medium and high skill categories, as well as the Sig. (2-tailed) value of 0.000, which demonstrates a substantial difference between pretest and post-test critical thinking abilities and student learning outcomes, demonstrates effectiveness. Based on these findings, it can be said that Think Pair Share-oriented E-LKPD can enhance students' critical thinking abilities concerning chemical equilibrium content.